Ensiling Reduces Seed Viability: Implications for Weed Management - Hahn, Juliane; de Mol, Friederike; Müller, Jürgen (Frontiers in Agronomy, 2021)
Ensiling, a lactic acid fermentation process, is mainly used to preserve biomass. In addition, it has been shown to affect seed viability of some plant species. The extent to which this makes ensiling suitable as a weed control measure, however, has not yet been determined. Both the range of controllable species and the parameters of an ensiling process that safely kills seeds are still undefined. We aimed to determine the effect of varying substrate and ensiling conditions on the seed viability of 10 species selected to represent a wide range of different seed traits. Five different types of silages were made from maize or mixtures of wildflower and maize biomass and ensiled in lab-scale silos for 8 months. The pure maize silages were prepared under conditions either ideal or suboptimal for ensiling forage. Seeds of important weeds (Chenopodium album, Abutilon theophrasti) and of species from a wildflower mixture suitable for ensiling and biogas production (Cichorium intybus, Daucus carota, Echium vulgare, Malva alcea, Malva sylvestris, Melilotus albus, Melilotus officinalis) were tested. Seed viability was determined using a combination of tetrazolium and germination tests. Ensiling reduced seed viability across all 10 species significantly. Seed-killing efficacies of ensiling, however, differed widely among the species studied, largely related to whether the species could produce hard (physically dormant) seeds. Seeds from species without hardseededness were completely inactivated by ensiling, while the seed-killing efficacies for hardseeded species ranged from 5 to 60%. Variation in ensiled substrate and ensiling conditions had no consistent effect on seed survival. We concluded that ensiling has the potential to sustainably reduce seed viability of a wide range of species and therefore should be adopted as a component of integrated weed management in organic agriculture.